A report of the 2018 regional election in South Korea. Issue 3 (26th May 2020) - Jung, Kwangho; Kang, Youngju
ABSTRACT: The 2018 regional election in South Korea brought a tremendous political victory for the liberal Democratic Party of Korea (DPK) and a dramatic loss for the conservative Liberty Party Korea (LPK). The DPK won 14 out of 17 gubernatorial and metropolitan races, 151 out of 226 (69%) elections for executive office at the municipal level, 652 out of 824 (79%) provincial council seats, and 1, 638 out of 2, 926 (56%) municipal council seats. DPK's triumph can be ascribed to the aftermath of the impeachment of the last president Park Geun-Hye and high approval rates for the current DPK president Moon Jae-In. Despite DPK's extraordinary victory, LPK managed to keep some of its electoral strongholds. In addition, the proportion of elected female and young candidates remained very low even though the number of female and young candidates has risen over the past two decades.